Odpowiedzi

2010-03-13T16:31:23+01:00
A) x+2(x-3)= dla x = -5
= x+2x-6 =
= -5 + 2*(-5)-6 =
= -5-10-6 = -21
b) 4a-2(a-5)= dla a = 10
= 4a-2a+10 =
= 4*10-2*10+10 =
= 40-20+10 = 20+10 = 30
c) 20+5(7-b)= dla b = 3,5
= 20+35-5b =
= 20+35-5*3,5 =
= 55-17,5 = 37,5
2010-03-13T16:33:10+01:00
A) -5+2(-5-3)=-21
b) 5a-10
5*10-10=40
c) 55-b=55-3,5=51,5
2010-03-13T16:35:11+01:00
A) x+2(x-3)= dla x = -5
x+2x-6=(-5)+2×(-5)-6=-15-6=-21
b) 4a-2(a-5)= dla a = 10
4a-2a-10=4×10-2×10-10=40-20-10=10
c) 20+5(7-b)= dla b = 3,5
20+35-5b=20+35-5×3,5=55-17,5=37,5